Jeoffry$1 (Bs Christmass - Bailey, Mary Bryant; Sayles, Elizabeth (New York : Farrar Straus Giroux, 2002)
A kind cat helps a farmer find the right Christmas tree and assists Santa Claus in delivering a Christmas feast to many animals.
Keywords: Cats -- Fiction; Christmas -- Fiction; Christmas trees -- Fiction; Santa Claus -- Fiction; Animals -- Fiction; Stories in rhyme